2005
DOI: 10.1128/iai.73.3.1321-1329.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vaccine Candidate Peptides in the NcSRS2 Surface Protein ofNeospora caninumby Using CD4+Cytotoxic T Lymphocytes and Gamma Interferon-Secreting T Lymphocytes of Infected Holstein Cattle

Abstract: Previously, our laboratory showed that Holstein cattle experimentally infected with Neospora caninum develop parasite-specific CD4 ؉ cytotoxic T lymphocytes (CTL) that lyse infected, autologous target cells through a perforin-granzyme pathway. To identify specific parasite antigens inducing bovine CTL and helper T-lymphocyte responses for vaccine development against bovine neosporosis, the tachyzoite major surface proteins NcSAG1 and NcSRS2 were targeted. In whole tachyzoite antigen-expanded bovine T-lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…The primary purpose of the experiments as designed was not to determine a mechanism of immunity to N. caninum subunits nor compare types of immunization parameters, such as different adjuvants, routes of immunization, or specific immunogen types. Before moving forward with efficacy trials in pregnant cattle, we simply were asking, "Can NcSRS2 subunits be designed and administered that will induce T-lymphocyte activation and IFN-␥ secretion similar to what we and others had observed when experimentally infecting cattle with N. caninum tachyzoites (36,39,43)?" Previous studies with collaborators showed that the DNA immunization procedure used in the present study could induce antigenspecific T-cell responses, optimally detected in short-term Tlymphocyte lines (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary purpose of the experiments as designed was not to determine a mechanism of immunity to N. caninum subunits nor compare types of immunization parameters, such as different adjuvants, routes of immunization, or specific immunogen types. Before moving forward with efficacy trials in pregnant cattle, we simply were asking, "Can NcSRS2 subunits be designed and administered that will induce T-lymphocyte activation and IFN-␥ secretion similar to what we and others had observed when experimentally infecting cattle with N. caninum tachyzoites (36,39,43)?" Previous studies with collaborators showed that the DNA immunization procedure used in the present study could induce antigenspecific T-cell responses, optimally detected in short-term Tlymphocyte lines (28).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four nonpregnant female or castrated male yearling Friesian-Holstein cattle (Bos taurus) were selected for MHC-I and MHC-II NcSRS2 responder haplotypes as identified previously (39) ( Table 1). The bovine lymphocyte antigen class I haplotypes and DRB3 alleles were characterized by microarray typing as previously described (31,39). Animals were housed and cared for in accordance with the animal care and use regulations of Washington State University, Pullman, WA, and the animal welfare committee guidelines of the Kimron Veterinary Institute, Bet-Dagan, Israel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In cattle, the situation is less polarized, and the classical roles of many cytokines in the laboratory mouse do not extrapolate entirely or at all to cattle. 25 Therefore, a suitable approach for the selection of suitable vaccine candidates would be to perform in vitro assays with bovine CD4(+) cytotoxic lymphocytes, as done by Staska et al 26 The candidate polypeptides inducing the highest level of IFN-γ secretion should then be retained for further assessment.…”
Section: Vaccination Against Neosporosismentioning
confidence: 99%